American odyssey : the United States in the twentieth century - Nash, Gary B. (New York : Glencoe/McGraw-Hill, 1999)
A history of the United States in the twentieth century, featuring sociological and cultural events, as well as strictly historical, and using many pertinent literary excerpts
Includes multimedia activities
Includes bibliographical references and index
Keywords: United States -- History -- 20th century; United States -- History -- 20th century